PENGARUH PELATIHAN DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KERJA KARYAWAN PT INBISCO NIAGATAMA SEMESTA MEDAN - Rini handayani; Rosniwaty Br. Bangun (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2022)
This study aims to determine the effect of training on job loyalty, determine the effect of environment on work loyalty, and determine the effect of training and work environment simultaneously on job loyalty at PT Inbisco Niagatama Semesta Medan. This research is a descriptive quantitative questionnaire instrument, the research population is 40 permanent employees, the sample uses a saturated sample so that the research sample is as much as. 40 people. The results of the research that the tcount coefficient of the Training variable is 2,363 and the ttable value is 2,022, the tcount > ttable (2,363 > 2.022) and the sig value < 0.05 (0.023 < 0.05), the coefficient value of the tcount variable Work Environment is 13,827 and the ttable value is 2,022, the value of tcount > ttable (13,827 > 2,022) and sig < 0.05 (0.000 < 0.05). Furthermore, the Fcount value of the Training and Work Environment variable is 11,339 and the value of Ftable is 2,845, the value of Fcount > Ftable (11,339 > 2.845 and the value of sig < 0.05 (0.000 < 0.05) The RSquare value is 0.690 or R2 x 100% of 69.00% , meaning that the research variable explains about job loyalty by 69.00% while the remaining 31.00% affects other variables.The conclusions of the research, training has a significant effect on job loyalty, environment has a significant effect on job loyalty and simultaneously training and work environment has a significant effect on loyalty Work at PT Inbisco Niagatama Semesta Medan